Factors affecting the acceptance of tele-psychiatry: a scoping study - Reyhane Izadi; Mohammad Amin Bahrami; Mohsen Khosravi; Sajad Delavari (BMC, 2023)
Abstract Background In today's digital world, providing services through telemedicine has become an essential issue in health systems, and the Covid-19 pandemic has made this necessity even more apparent. On the other hand, mental health services are needed more than ever, and their nature makes their delivery via telemedicine more feasible than other specialized services. This study aimed to determine the factors affecting the acceptance of telemedicine among users of this technology in the field of mental health. Methods This article is a scoping review based on the PRISMA guidelines and without any time limit until June 20, 2022. The search was performed in PubMed, Scopus, Web of Science, and PsycINFO databases using keywords related to the three fields of telemedicine, acceptance, and mental disorders. Two authors independently selected the studies based on inclusion and exclusion criteria. Then the data were collected using a data extraction form, and finally, the results were determined using the content analysis method. Results Five main factors affect the acceptance of telemedicine among users of this technology in the field of mental health: perceived effectiveness, users' understanding of the effects of telemedicine on the quality and outcomes of care delivery, technological aspects, organizational change capacity, the nature of the disease and psychological and psychosocial factors. These main factors are associated with 21 related sub-factors. Conclusions Revealing the factors affecting the acceptance of telemedicine among recipients and providers of services, as key actors in health systems, can help managers and policymakers to successfully implement telemedicine in the less-regarded field of mental health, especially in the early stages.